Considerations for the Development of a Substance-Related Care and Prevention Continuum Model - Perlman, David C.; Jordan, Ashly E. (Frontiers in Public Health, 2017)
There are significant gaps in the identification and engagement in care and prevention services of people who use illicit substances. Care continuum models have proven to be useful tools in the evaluation of care for HIV and other conditions; numerous issues in substance-related care and prevention resemble those identified other continua models. Systems of care for substance misuse and substance use disorders (SUDs) can be viewed as consisting of a prevention and care continuum, reflecting incidence and prevalence of substance misuse and SUDs, screening and identification, medical and psychosocial evaluation for treatment, engagement in evidence based treatment, treatment retention, relapse prevention, timeliness of step completion and measures of overall and substance-use-related-specific morbidity and mortality. Care and prevention continuum models could potentially be applied at program, local, regional, state and national levels. We discuss important lessons that can be drawn from applications of continuum models in other fields. The development and use of a substance-related care and prevention continuum may yield significant patient care, program evaluation and improvement, and population-level benefits.